Report for the year 1943-44 - Layton, Eleanor Dorothea, Lady
1944-03-14 035-0082-005 through awards of the Juan Luis Vives Scholarship Trust, many of them are enabled to continue their studies at secondary schools, universities and polytechnics, becoming teachers and nurses, etc. The older boys are also taking their part in work of national importance, and 16 are now in the services—with the R.A.F., Pioneer Corps or training for the Merchant Navy. A number of them are also being trained through the Juan Luis Vives Scholarship Trust, and a considerable amount of talent has been found to enable them to take up training in engineering, science, art and architecture. HOSTELS Three hostels still remain—Caerleon, Carshalton and Finchley. Caerleon — Since last year this centre has been able to billet in outside homes many of the children hitherto in their care and only a few remain in the hostel, which, though much reduced. is still maintained and considerably helped by friends living in the locality. Carshalton is reorganised on a very sound basis and helps considerably with its own support among friends and local helpers. It has mostly young children. Finchley — Fourteen young children are still going to school, and it will be some time before they will be old enough to be placed in billets, which is not so expensive as keeping a special home for them. This hostel is maintained almost entirely by the National Joint Committee for Spanish Relief and the British Foster Parents Scheme. HEADQUARTERS The work of the Central Office continues to be handled by a small and devoted staff, and regular meetings of the Officers and Executive Committee take place to make all decisions on policy. FINANCE We are gradually building up a reserve to cover the cost of repatriation when the time comes, but so far it is very small, and, apart from this, the donations received from our supporters are only just sufficient to enable us to carry on the current work. The Committee is immeasurably grateful for this help, and the many friends and organisations who have helped to make it possible for the work to continue for so long in spite of the many difficulties facing us. Our responsibilities, however, remain until the war is over, and funds are urgently needed. DOROTHEA LAYTON, Hon. Secretary. 39, Victoria Street, S.W.1. 292/946/35/82(v)